Strategic Significance of CPEC: A Game Changer for Pakistan - Malik Khurram Shahzad; Prof. Dr. Umbreen Javaid (Journal of Political Studies, 2020)
This paper is intended to explore the strategic significant of CPEC for Pakistan while hypothesizing that it is a game changer for Pakistan. For testing the hypothesis, researcher reviewed secondary data sources including books, articles published in national and international journals, official reports and other relevant documents. The findings are presented in five themes i.e. economic impacts of CPEC, social impacts of CPEC, impacts on energy crises, impacts on foreign policy and impacts on balance of power and security. The findings indicated that CPEC is of great significance for Pakistan because of its relevance with many positive outcomes for socio-economic development of the country and for enhancing people’s standard of living and their quality of life. However, there are some of the potential gray areas which can be dealt with proper planning, political vision and progressive working by relevant Pakistani stakeholders.